2012
DOI: 10.1186/1475-2840-11-144
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of steroidogenic acute regulatory protein in rat aortic endothelial cells attenuates palmitic acid-induced inflammation and reduction in nitric oxide bioavailability

Abstract: BackgroundEndothelial dysfunction is a well documented evidence for the onset of atherosclerosis and other cardiovascular diseases. Lipids disorder is among the main risk factors for endothelial dysfunction in these diseases. Steroidogenic acute regulatory protein (StAR), one of the cholesterol transporters, plays an important role in the maintenance of intracellular lipid homeostasis. However, the effect of StAR on endothelial dysfunction is not well understood. Palmitic acid (PA) has been shown to decrease e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 47 publications
1
17
0
Order By: Relevance
“…This is in agreement with several studies that suggest a link between these three proinflammatory cytokines and PA-induced inflammation [26, 27]. For example, Staiger et al reported palmitate-induced interleukin-6 expression in human coronary artery endothelial cells and suggested a potential contribution of palmitate to vascular inflammation [27].…”
Section: Discussionsupporting
confidence: 91%
“…This is in agreement with several studies that suggest a link between these three proinflammatory cytokines and PA-induced inflammation [26, 27]. For example, Staiger et al reported palmitate-induced interleukin-6 expression in human coronary artery endothelial cells and suggested a potential contribution of palmitate to vascular inflammation [27].…”
Section: Discussionsupporting
confidence: 91%
“…Augmented levels of serum inflammatory cytokines and macrophages infiltration in adipose tissue have been proven as the most common appearances of obesity-linked inflammation [Weisberg et al, 2003;Gregor and Hotamisligil, 2011]. We have previously reported that overexpression of StAR in rat aortic endothelial cells attenuated PA-induced reduction in nitric oxide bioavailability [Tian et al, 2012]. We have previously reported that overexpression of StAR in rat aortic endothelial cells attenuated PA-induced reduction in nitric oxide bioavailability [Tian et al, 2012].…”
Section: Discussionmentioning
confidence: 97%
“…In macrophages, Star overexpression impacts positively on the lipid-related phenotype of these cells, since it represses a number of genes involved in cholesterol biosynthesis and LDL uptake and markedly increases the expression of ABCA1, strongly suggesting that Star increases sterol efflux to apoAI (Taylor et al 2010). This protein has also been shown to be a protective molecule for endothelial dysfunctions in aortic endothelium (Tian et al 2012). Interestingly, presence of STAR protein has also been described in human liver cells, where it appears to be involved in cellular cholesterol homeostasis, representing a potential therapeutic target in the management of hyperlipidemia (Hall et al 2005).…”
Section: Discussionmentioning
confidence: 99%